MHC1/LILRB1 axis as an innate immune checkpoint for cancer therapy - Hu, Ziyi; Zhang, Qiaodong; He, Zehua; Jia, Xiaojian; Zhang, Wencan; Cao, Xu (Frontiers in Immunology, 2024)
Immune checkpoint blockades (ICBs) have revolutionized cancer therapy through unleashing anti-tumor adaptive immunity. Despite that, they are usually effective only in a small subset of patients and relapse can occur in patients who initially respond to the treatment. Recent breakthroughs in this field have identified innate immune checkpoints harnessed by cancer cells to escape immunosurveillance from innate immunity. MHC1 appears to be such a molecule expressed on cancer cells which can transmit a negative signal to innate immune cells through interaction with leukocyte immunoglobulin like receptor B1 (LILRB1). The review aims to summarize the current understanding of MHC1/LILRB1 axis on mediating cancer immune evasion with an emphasis on the therapeutic potential to block this axis for cancer therapy.Nevertheless, one should note that this field is still in its infancy and more studies are warranted to further verify the effectiveness and safety in clinical as well as the potential to combine with existing immune checkpoints.